Political Connections and Corporate Bailouts - FACCIO, MARA; MASULIS, RONALD W.; McCONNELL, JOHN J. (Journal of Finance, 2006)
ABSTRACT We analyze the likelihood of government bailouts of 450 politically connected firms from 35 countries during 1997–2002. Politically connected firms are significantly more likely to be bailed out than similar nonconnected firms. Additionally, politically connected firms are disproportionately more likely to be bailed out when the International Monetary Fund or the World Bank provides financial assistance to the firm's home government. Further, among bailed‐out firms, those that are politically connected exhibit significantly worse financial performance than their nonconnected peers at the time of and following the bailout. This evidence suggests that, at least in some countries, political connections influence the allocation of capital through the mechanism of financial assistance when connected companies confront economic distress.